A low-cost and open-source mini benchtop centrifuge for molecular biology labs. (October 2022) - Soma Poór, Viktor
Graphical abstract: Abstract: The aim of this manuscript is to provide all the necessary information to build a simple benchtop mini centrifuge that is able to remove droplets and liquid film from the inner wall of PCR tubes and PCR strips following vortexing. Users can choose between two rotors: one can hold up to six tubes (1.5/2 ml, or 500 µl and 200 µl tubes with adapters) or two PCR strips. The design consists of only three printed parts (optimized to be printed without supports) and cheap off-the-shelf components (80 mm computer fan, switches, food container and power supply). It can be assembled with basic soldering skills, no programming needed. While the total cost of materials is only 20 €, when compared to its commercial counterparts, this DIY benchtop spinner was equally capable to remove droplets. Comparing noise levels this model was quieter than an Eppendorf 5424, BioSan MSC-6000 or Kisker biotech centrifuges. Because it is designed to perform a very generic and common task, it could be useful for a very wide array of laboratories and researchers: molecular biology, genetics, microbiology, student labs, biohacking labs, etc.